Implementasi Aplikasi Web MySaku Dalam Meningkatkan Literasi Keuangan Siswa SMP Utama YPPG - Yodi Dwi Cahyo; Agustinus Beda Buraq; Aziz Nugroho; Erland Radithya Putra; Ilham Syahgani; Lintar Yan Zuhara; Lucky Yan Zuhara; Rendy Wijaya; Rizky Andriyanto; Simon Simarmata (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Financial literacy is a fundamental skill that needs to be introduced from an early age, especially for junior high school students who begin to have freedom in managing their pocket money. However, many students still lack an understanding of recording income and expenses as well as distinguishing between needs and wants. Based on observations at SMP Utama Yayasan Pendidikan Putra Gumanti (YPPG) Pondok Aren, students were not accustomed to managing pocket money in a planned manner. This community service activity aims to improve students’ financial literacy through the use of the MySaku web application as a simple and practical financial recording tool. The implementation method applied educational, participatory, and applicative approaches through material delivery, application demonstrations, and direct assistance to students. The results show that students were able to understand basic financial management concepts and use the MySaku application independently. Therefore, the MySaku web application can serve as an effective learning medium to improve financial literacy among junior high school students.